Advancing organ transplantation through HIV-to-HIV transplantation. Issue 4 (August 2021) - Fuller, Risa; Rana, Meenakshi M.
Abstract : Purpose of review: Persons living with HIV (PLWH) have a life expectancy that is nearly equivalent to the general population, and thus are facing health conditions associated with normal aging as well as long-term HIV infection. End-organ disease is associated with significant morbidity and mortality and solid organ transplantation (SOT) may be a viable option for many PLWH. We review the history and recent updates in SOT in PLWH, specifically focusing on HIV-to-HIV transplantation. Recent findings: Following promising data out of South Africa and to expand the donor pool, the United States passed the HIV Organ Procurement Equity (HOPE) Act, allowing for HIV-to-HIV SOT. Preliminary data to date, especially in HIV-to-HIV kidney transplantation, suggest overall excellent patient and graft survival outcomes with no HIV breakthrough infection. Summary: Preliminary HIV D+R+ SOT data to date suggest promising patient outcomes and no significant adverse events to recipients or living donors. This is an important step in expanding the donor pool and increasing opportunity for SOT in PLWH.